Sustainable management of oil palm waste: perspective of smallholder / Muhammad Amru Al- As Rohim and Nur Aziera Ruslan - Rohim, Muhammad Amru Al- As; Ruslan, Nur Aziera (Faculty of Plantation and Agrotechnology, 2018)
Oil palm industry in Malaysia has emerged rapidly with the total estimated planted area about5110713 which contributes fresh fruit bunch about 17.89 tan per hectare made Malaysia become world’s second premium producer of oil palm with the 60% managed by private domain while others 40% managed by smallholders. Improper of oil palm waste management by smallholders due to lack of awareness about potential of oil palm waste and cooperation by the smallholders in managing oil palm waste caused few problems which abundance of oil palm waste that contributed to health and environmental problems due to estimated 90% of oil palm turn into waste products like EFB. Fibres, shells and liquid effluent while 10% turn to oil. Problem arises can be solved by identifying factors affecting oil palm smallholders in practicing sustainable management of oil palm waste. Theory of Planned Behaviour which consist of attitude, subjective norms and perceived behaviour control has being used as conceptual framework for conducted survey in order to examine the perspective of smallholders toward sustainable management of oil palm waste. Felda Trolak Utara in Sungkai Perak has been chosen to conduct the survey due to its location and condition fit the problem arises with the 250 of total population made the respondent targeted is about 152 sample based on Krejcie and Morgan table. Statistical Package for Social Science was being used for correlation and multiple regression analysis. The results for correlation analysis were significant relationship for attitude and subjective norms variables toward dependent variable while for multiple regression it was attitude variable become the most influenced factor toward sustainable management of oil palm waste among smallholders. Hence, the smallholders that have positive attitude and strong subjective norms toward oil palm waste management will practicing sustainable management of oil palm waste.